Ethical finances as a tool of solidarity economy. The experiencie of Coop57 - Gassiot Ballbè, Raimon (Cuadernos de Trabajo Social, 2013)
This article analyzes the role of ethical finances as a tool for development of the solidarity economy, an economy that seeks to satisfy the needs of people, has a democratic governance and an equitable distribute of wealth generated, and incorporates principles of social and environmental sustainability. It makes a brief analysis of the current crisis and the role it has played the conventional financial system, proposed the solidarity economy and the ethical finances as an alternative with potential for social transformation and focuses on explaining the experience of the cooperative financial services Coop57. Finally, proposes some ideas of how the discipline and practice of social work can contribute to the development of solidarity economy.
Keywords: economic solidarity; ethical finances; social transformation; cooperative movement; self-management; mutualism.